Deregulation of cell proliferation by polycyclic aromatic hydrocarbons in human breast carcinoma MCF-7 cells reflects both genotoxic and nongenotoxic events - Plísková, Martina; Vondrácek, Jan; Vojtesek, Borivoj; Kozubík, Alois; Machala, Miroslav (Toxicological sciences, 2005)
Polycyclic aromatic hydrocarbons (PAHs), such as benzo[a]pyrene (BaP), are carcinogens suggested to be involved in development of human cancer. Several recent studies have reported that PAHs can activate estrogen receptors (ER), either directly or indirectly by producing estrogenic metabolites. We hypothesized that the activation of ER by PAHs or their metabolites could induce cell proliferation in estrogen-sensitive cells. In the present study, we found that two PAHs, benz[a]anthracene (BaA) and BaP, can stimulate proliferation of human breast carcinoma MCF-7 cells at concentrations 100 nM and higher. This effect was ER-dependent, because it was blocked by the pure antiestrogen ICI 182,780. Although both PAHs partially inhibited S-phase entry and DNA synthesis induced by 17beta-estradiol, they stimulated S-phase entry when applied to MCF-7 cells synchronized by serum deprivation. This was in contrast with model antiestrogenic aryl hydrocarbon receptor ligand, 2,3,7,8-tetrachlorodibenzo-p-dioxin, which fully suppressed S-phase entry. BaP, which is a strong mutagen, was found to induce p53 tumor suppressor expression, a partial S-phase arrest and at higher concentrations also cell death. Pifithrin-alpha, a synthetic inhibitor of p53 activity, abolished both S-phase arrest and apoptosis induced by genotoxic PAHs, and it potentiated the proliferative effect of BaP. Thus, both genotoxic and nongenotoxic events seem to interact in the effects of BaP on cell proliferation. Taken together, our data indicate that both BaA and BaP can stimulate cell proliferation through activation of ER. The proliferative effects of these carcinogenic compounds might contribute to tumor promotion in estrogen-sensitive tissues.
Keywords: nádorový supresorový protein p53; karcinogeny; Cell Cycle; Drug Interactions; nádorové buněčné linie; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; Breast Neoplasms; Bromodeoxyuridine; epigeneze genetická; receptory pro estrogeny; benz(a)anthraceny; DNA Replication; Epigenesis, Genetic; replikace DNA; fulvestrant; toluen; Cell Proliferation; Cell Line, Tumor; Tumor Suppressor Protein p53; Benzothiazoles; buněčný cyklus; Benzo(a)pyrene; Carcinoma; antagonisté estrogenu; Estrogen Antagonists; Thiazoles; bromodeoxyuridin; ženské pohlaví; Fulvestrant; Humans; Receptors, Estrogen; Carcinogens; Estradiol; thiazoly; benzopyren; viabilita buněk; Cell Survival; nádory prsu; proliferace buněk; lékové interakce; Benz(a)Anthracenes; Toluene; Female; estradiol; lidé; benzothiazoly; karcinom